Development of osmotically dehydrated banana peel strips from the saba variety (Musa paradisiaca Linn. Var. compressa) - Hormigos, Helen May E.; Rillo, Belen O. (1983)
This study aimed at developing a banana peel product utilizing the saba variety (Musa paradisiaca Linn. var. compressa). This was carried out first by determining the best stage of maturity - unripe, rareripe, or ripe stage - to use for banana peel strips. The soaking time and the optimum level of syrup concentration (using 50, 60, and 70% brown sugar solutions, by weight) were then determined. Finally, the drying time curve was constructed in order to determined the time required in achieving the optimum moisture content level (6-8% or 10-12%, dry basis) for the banana peel strips. Results of the study showed that saba banana peels at the rareripe stage, cut into strips, immersed for 1 hour in a 60% brown sugar solution, and then dried for 165 minutes at a temperature of 140-160°F in a medium-size cabinet dried gave the most acceptable banana peel product. Objective tests showed that the product had an ash content of 2.24%, a crude fiber content of 5.92%, and a moisture content of 11.2%. Sensory evaluation showed that the product had a "brownish yellow" color, a texture described as between "chewy" and "though and moist", and a "slightly sweet" flavor. The product had a mean hedonic scale rating corresponding to "like slightly".
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Banana products; Bananas